PENINGKATAN MUTU PENDIDIKAN TINGGI BERBASIS MERDEKA BELAJAR KAMPUS MERDEKA - Raharja, Reza Mauldy; Sutrisno; Bafadal, Ibrahim; Sunarni (Jurnal Penjaminan Mutu, 2024)
Abstract This research aims to determine the improvement in the quality of higher education based on the Independent Campus Learning (MBKM) policy. One form of policy of the Minister of Education and Culture in improving quality is through the MBKM policy. This study is an idea presented based on literature reflection where data is collected through literature review, analyzed and presented in discussion. Improving the quality of human resources through improving the quality of education is an investment made by the government. The Independent Campus Learning Policy (MBKM) is a real effort made by the government to answer future challenges. There are four main MBKM programs, namely ease of opening new study programs, changes to the higher education accreditation system, ease of state universities becoming legal entity PTNs and the right to study three semester study programs outside. The concept of implementing MBKM is to create an autonomous and flexible learning process in higher education so as to create an innovative learning culture that suits student needs, and is able to encourage students to master various knowledge that is useful for entering the world of work, as well as providing opportunities for students to determine their major they will take.